PEMBUATAN MIE KERING DENGAN FORTIFIKASI EKSTRAK BUAH KARAMUNTING (Rhodomyrtus tomentosa, (Aiton) Hassk.) - Riani Sari Sembiring; Dini Novita Sari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2021)
This study aims to determine the physical, chemical, sensory characteristics of dry noodles and to test the antioxidant activity using the DPPH method. This research method used a randomized block design (RBD) using one factor, namely the addition of Caramunting Fruit Extract (Rhodomyrtus Tomentosa) W. Ait. Hassk (0 ml, 25ml, 50ml, 75ml and 100ml). The treatment in the study had a significant effect on chemical analysis (moisture, ash, protein, and carbohydrate content), physical analysis (Rehydration Power), sensory analysis (color, aroma, taste, and texture) and antioxidant activity tests using the DPPH method, but had no effect. significant on fat content and Water Absorption Measurement. The average water content, ash, protein, fat, and carbohydrates produced were 4.41%, 6.14%, 26.11%, 3.51%, and 59.77%. Measurement of Water Absorption and Rehydration Power, namely 54.03% and 135.15%. The average score of the panelists' preference for taste, texture, aroma and color in Fortified Dry Noodles Caramunting Fruit Extract (Rhodomyrtus Tomentosa) W. Ait. Hassk, namely 3,342%, 3,446%, 3,444% and 3,386%. The results of the test for antioxidant activity of Fortified Dry Noodles Extract of caramunting fruit (Rhodomyrtus tomentosa) W. Ait. Hassk showed the potential for antioxidants with IC50 values ​​of 2652.537 ppm, 1535.224 ppm, 544.8203 ppm, 517.7615 ppm, and 396.8802 ppm, respectively. Antioxidant levels after processing decreased compared to levels of Antioxidants in Karamunting fruit seeds of 99.52 ppm. The use of heat in the processing reduces the antioxidant content of processed products.